2013
DOI: 10.4049/jimmunol.1203233
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotide Treatment Enhances the Recovery of Acute Lung Injury through IL-10–Secreting M2-like Macrophage-Induced Expansion of CD4+ Regulatory T Cells

Abstract: MicroRNAs (miRNAs) have been shown as an important regulator in the pathologies of acute lung injury (ALI). However, the potential effect of miRNA-based therapeutic studies in ALI remains poorly understood. We assessed the effect of antisense oligonucleotides (ASOs) against miR-155 on the development of ALI using a murine ALI model. We found that miR-155 ASO treatment could enhance the recovery of ALI as evidenced by accelerated body weight back, reduced level of bronchoalveolar lavage (BAL) protein and proinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 59 publications
4
40
0
Order By: Relevance
“…In this study, we observed that IL-10 secretion in unstimulated and CSE-exposed cells was higher in COPD alveolar macrophages compared to controls, consistent with the switching of COPD alveolar macrophages towards the M2-like phenotype [39], which is anti-inflammatory and involved in tissue repair [40][41][42]. However, CSE reduced IL-10 secretion in TLR-stimulated cells from both groups; this suggests that CSE causes a suppression of this anti-inflammatory mechanism under conditions of bacterial exposure.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we observed that IL-10 secretion in unstimulated and CSE-exposed cells was higher in COPD alveolar macrophages compared to controls, consistent with the switching of COPD alveolar macrophages towards the M2-like phenotype [39], which is anti-inflammatory and involved in tissue repair [40][41][42]. However, CSE reduced IL-10 secretion in TLR-stimulated cells from both groups; this suggests that CSE causes a suppression of this anti-inflammatory mechanism under conditions of bacterial exposure.…”
Section: Discussionsupporting
confidence: 75%
“…We showed previously that miR-155, a proinflammatory miRNA, is differentially regulated by Akt kinases and plays a central role in M1 polarization of macrophages in several inflammatory models (22). Also, miR-155 was found to be important in the pathogenesis of LPS-induced lung injury (50). Yet, in the aseptic model of acidinduced lung injury, an increase in miR-155 expression was not necessary for the initial M1 polarization of macrophages, whereas a decrease in miR-155 levels was associated with the development of M2 phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Th17 cells and CD4 + CD25 + Foxp3 + Tregs not only exert opposite functions in immune responses, they also share reciprocal developmental pathways. Balancing CD4 + CD25 + Foxp3 + Tregs and Th17 cells in ALI may help maintain the immune system in the steady state and exhibit a therapeutic benefit for this disease …”
Section: Discussionmentioning
confidence: 99%